The potential use of probiotic and beneficial bacteria in the Brazilian dairy industry. Issue 4 (16th November 2018) - Colombo, Monique; Todorov, Svetoslav Dimitrov; Eller, Monique; Nero, Luís Augusto
Abstract : Scientific studies demonstrate the importance of intestinal microbiota to human health and how probiotic microorganisms can positively affect health when administered regularly and in adequate amounts. Probiotic bacteria can be part of fermented products and their functional importance is associated mainly with their metabolism. They are thought to benefit individuals to maintain their health and also to strengthen resistance against various types of diseases. The acceptance of probiotic cultures and products by consumers increased when these bacteria were marketed as natural cultures that help in digestion and health. Considering this, the food industry has an increasing demand for new candidates as probiotic cultures, and the dairy industry has a particular interest for fermented milks and other dairy products, since these are the most common food vehicles for probiotic cultures. Therefore, the dairy industries are increasingly seeking to improve their products with these beneficial bacteria. However, the legal peculiarities and excess of control agencies in Brazil makes the registration of these products and the collection of data very complex. Prospective analysis suggests that probiotic foods have the potential to effect a considerable expansion of the dairy industry, allowing the dairy sector to grow and for these products to be increasingly sought by consumers globally. For this, not only actions on research and innovation are necessary, but also official clarifications on the claims for considerations of microbiological security and functionality of these products. This review aims to elucidate important probiotic research regarding the isolation and characterization of beneficial cultures in Brazil, and to demonstrate the relevance of the dairy chain as a potential source of novel cultures for the development of new probiotic products to expand the Brazilian dairy industry.